Chitin induces upregulation of B7-H1 on macrophages and inhibits T-cell proliferation - Wagner, Claudia; Huber, Silke; Wirth, Stefanie; Vöhringer, David (European Journal of Immunology, 2010)
Chitin is a highly abundant glycopolymer, which serves as structural component in fungi, arthropods and crustaceans but is not synthesized by vertebrates. However, vertebrates express chitinases and chitinase-like proteins, some of which are induced by infection with helminths suggesting that chitinous structures may be targets of the immune system. The chitin-induced modulations of the innate and adaptive immune responses are not well understood. Here, we demonstrate that intranasal administration of OVA and chitin resulted in diminished T-cell expansion and Th2 polarization as compared with OVA administration alone. Chitin did not promote nor attenuate Th2 polarization in vitro. Chitin-exposed macrophages inhibited proliferation of CD4+ T cells in a cell-cell contact-dependent manner. Chitin induced upregulation of the inhibitory ligand B7-H1 (PD-L1) on macrophages independently of MyD88, TRIF, TLR2, TLR3, TLR4 and Stat6. Inhibition of T-cell proliferation was largely dependent on B7-H1, as the effect was not observed in cocultures with cells from B7-H1-deficient mice. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA.
Created from Fastlane, Scopus look-up
Keywords: B7-H1; Chitin; Macrophages; T-cell proliferation